New host plants records of Bactrocera carambolae Drew & Hancock, 1994 and Anastrepha spp. (Diptera: Tephritidae) in Brazil - Belo, Andressa P. D.; Rocha, Leide M. da S.; Corrêa, Jackson M. G.; Ferreira, Ricardo M. dos A.; Costa-Neto, Salustiano V. da; Sousa, Maria do S. M. de; Adaime, Ricardo; Lemos, Lailson do N. (Entomological Communications, 2020)
In this work we report five new host plants of Bactrocera carambolae Drew & Hancock, 1994 as well as new records of hosts of Anastrepha bahiensis Lima, 1937, Anastrepha fraterculus (Wiedemann, 1830), and Anastrepha striata Schiner, 1868 from samplings carried out in Mazagão county, Amapá-Brazil.